2016
DOI: 10.1071/wf15109
|View full text |Cite
|
Sign up to set email alerts
|

Places where wildfire potential and social vulnerability coincide in the coterminous United States

Abstract: The hazards-of-place model posits that vulnerability to environmental hazards depends on both biophysical and social factors. Biophysical factors determine where wildfire potential is elevated, whereas social factors determine where and how people are affected by wildfire. We evaluated place vulnerability to wildfire hazards in the coterminous US. We developed a social vulnerability index using principal component analysis and evaluated it against existing measures of wildfire potential and wildland-urban inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 67 publications
5
78
0
4
Order By: Relevance
“…The least vulnerable counties are located in New England and the upper Great Lakes. Results from the previous assessments 16,21,52 indicate similar spatial geographical patterns. Cutter and Finch 21 showed that the vulnerability is increasing in the southwest parts toward the U.S.-Mexico border regions of Texas in the last four decades, which can be due to the clustering of high vulnerable counties in that region, based on the SEVI calculated in this study.…”
Section: Socio-economicmentioning
confidence: 61%
See 3 more Smart Citations
“…The least vulnerable counties are located in New England and the upper Great Lakes. Results from the previous assessments 16,21,52 indicate similar spatial geographical patterns. Cutter and Finch 21 showed that the vulnerability is increasing in the southwest parts toward the U.S.-Mexico border regions of Texas in the last four decades, which can be due to the clustering of high vulnerable counties in that region, based on the SEVI calculated in this study.…”
Section: Socio-economicmentioning
confidence: 61%
“…This study aimed to generate a comprehensive SEVI; however, it still has some limitations. Although social vulnerability indices can efficiently describe broad-scale vulnerability, they fall short on integrating localized information related to exposure, sensitivity, and adaptive capacity that is often better collected using qualitative methods such as empirical methods and surveying 52,65 . Moreover, the calculated SEVI is based on only one point in time (the recent past), and the spatial patterns of socioeconomic vulnerability that were identified in this study represent the recent past.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extensive literature on social science related to wildfire issues (McCaffrey, 2015) has studied risk perception, mitigation decisions and perceived consequences (Champ & Brenkert-Smith, 2016;Champ, Donovan, & Barth, 2013;Dickinson, Brenkert-Smith, Champ, & Flores, 2015;Gordon, Luloff, & Stedman, 2012); community pre-fire mitigation (Cohn, Williams, & Carroll, 2008) and adaptive capacity ; residents' actions and adaptation (Brenkert- Smith, 2006); and community social diversity and vulnerability (Paveglio, Nielsen-Pincus, Abrams, & Moseley, 2017;Paveglio, Prato, Edgeley, & Nalle, 2016). However, work to assess wildfire risk by integrating social and natural systems is relatively new (Cutter, Boruff, & Shirley, 2003;Davies et al, 2018;Gaither, Goodrick, Murphy, & Poudyal, 2015;Gaither et al, 2011;Oliveira, Zêzere, Queirós, & Pereira, 2017;Parisien et al, 2016;Wigtil et al, 2016) or applied at limited geographic scales (Fischer, Kline, Ager, Charnley, & Olsen, 2014;Nielsen-Pincus et al, In review;Olsen, Kline, Ager, Olsen, & Short, 2017;Paveglio, Edgeley, & Stasiewicz, 2018;Paveglio et al, 2016), leaving a gap in our knowledge about large-scale transboundary risk in relation to behavioral response to fire. Our first goal is to understand where transboundary large fire events originate and how they spread through a mosaic of land tenures, management jurisdictions and fuel models, and quantify their impacts on the communities of three socially and biophysically distinct fire-prone regions of the western US.…”
Section: Introductionmentioning
confidence: 99%